A toughened composite for improving the anchoring of composite tensile armors of flexible risers - Mattedi, Rafael Pereira (2019)
The use of composite and nanocomposites is a growing trend in many industries such as aerospace, automotive and energy. For many applications, the adhesion between structures for efficiently transferring loads is a difficult problem to solve. In oil and gas segment, for instance, a common technique used for anchoring the tensile armors of flexible riser within the end fitting is through an embedded epoxy since it provides good mechanical and chemical resistance. Even though, cracks and defects can arise in the epoxy block during operations or mounting at epoxy curing step, and such cracks could affect the anchoring performance, in particular for carbon fiber composite armors (CFA). In this context, this work proposes the improvement of the epoxy for anchoring the CFA, with a focus on the mechanical and adhesion properties. An analytical model is developed for CFA anchoring mechanism and verified by numerical analysis to evaluate the sensitivity of the system to the epoxy characteristics. Thus, the increase of these properties is proposed by adding multi-walled Carbon Nanotubes (MWCNTs) and some experiments are carried out with neat and toughened epoxies to characterize the gain of mechanical and adhesive properties. Then, nanotubes morphology and the matrix homogeneity are expertized to correlate with mechanical results. The research confirmed an improvement of anchoring resistance by toughening the epoxy matrix with MWCNTs.